Abjadpedia: Solusi Media Edukatif untuk Mengatasi Kesulitan Menulis Anak Dysgraphia: Abjadpedia: An Educational Media Solution to Overcome Writing Difficulties in Children with Dysgraphia - Ahmad Yusup Yudhoyono; Mimbar Oktaviana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Writing is a fundamental skill essential for elementary school children. However, many children experience writing difficulties, also known as dysgraphia, which negatively impacts their academic achievement and development. Findings from the Sanggar Merah Merdeka Surabaya community center indicate that several children exhibit writing difficulties. This demonstrates the need for innovative interventions that are not only therapeutic but also engaging and contextual to motivate children to learn to write. This study employed a one-group pretest-posttest experimental design with 7 children participating. The research instrument was developed based on DSM-5 criteria and validated by five expert judges, including psychologists and educators of children with special needs. The intervention used Abjadpedia, a fine-motor game-based approach to letter recognition. Data were analyzed using the Wilcoxon Signed Rank Test due to the small sample size and non-normal distribution. The results showed a significant improvement in writing ability following the intervention using Abjadpedia. The average pre-test score of 3.00 increased to 7.57 in the post-test, with a significance level of <0.05. This demonstrates the effectiveness of using Abjadpedia in helping children recognize letter patterns and improve fine motor coordination. Abjadpedia has proven effective as an innovative learning tool for improving the writing skills of children with dysgraphia. This innovation can be implemented as an alternative inclusive education intervention in elementary learning environments.